2022
DOI: 10.1186/s13756-022-01122-x
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis: emerging pathogens and antimicrobial resistance in Ethiopian referral hospitals

Abstract: Background Sepsis due to multidrug resistant (MDR) bacteria is a growing public health problem mainly in low-income countries. Methods A multicenter study was conducted between October 2019 and September 2020 at four hospitals located in central (Tikur Anbessa and Yekatit 12), southern (Hawassa) and northern (Dessie) parts of Ethiopia. A total of 1416 patients clinically investigated for sepsis were enrolled. The number of patients from Tikur Anbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
6
23
1
Order By: Relevance
“…Patients with methicillin-resistant Staphylococcus aureus had the greatest mortality rate, 47.5%, which was strongly associated with a higher chance of dying [ 22 ]. Similar study was done by Legese et al and found Klebsiella pneumoniae (26.1%), Klebsiella variicola (18.1%), and Escherichia coli (12.4%) as the major causative agent in 1416 blood culture [ 23 ]. Our study showed Staphylococcus aureus (14.0%) as the major causative organism, followed by Pseudomonas (8.0%) and then Klebsiella pneumoniae and Escherichia coli, both 2.0%, each amongst the blood culture positive plates.…”
Section: Discussionsupporting
confidence: 71%
“…Patients with methicillin-resistant Staphylococcus aureus had the greatest mortality rate, 47.5%, which was strongly associated with a higher chance of dying [ 22 ]. Similar study was done by Legese et al and found Klebsiella pneumoniae (26.1%), Klebsiella variicola (18.1%), and Escherichia coli (12.4%) as the major causative agent in 1416 blood culture [ 23 ]. Our study showed Staphylococcus aureus (14.0%) as the major causative organism, followed by Pseudomonas (8.0%) and then Klebsiella pneumoniae and Escherichia coli, both 2.0%, each amongst the blood culture positive plates.…”
Section: Discussionsupporting
confidence: 71%
“…The diagnostic criteria were positive blood bacterial culture, clinical symptoms and signs of bacterial infection, and abnormal laboratory test results (blood routine, C-reactive protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6) and other infection indicators) [ 8 ].…”
Section: Objects and Methodsmentioning
confidence: 99%
“…e subjects of this study were children diagnosed with Raoultia ornithine septicemia in the department of neonatology of our hospital from July 2020 to December 2021. e diagnostic criteria were positive blood bacterial culture, clinical symptoms and signs of bacterial infection, and abnormal laboratory test results (blood routine, C-reactive protein (CRP), procalcitonin (PCT), interleukin-6 (IL-6) and other infection indicators) [8].…”
Section: Research Objectsmentioning
confidence: 99%
“…In a non nationally representative data from Mozambique, S. aureus, E. coli and non-typhoidal salmonella dominated [78], and in Ethiopia [79] with a positive culture yield of 40.6% with Klebsiella and E. coli being the commonest, while Staph aureus and Klebsiella predominated in a Uganda report [80].…”
Section: Discussionmentioning
confidence: 93%